An improved read-assist energy efficient single ended P-P-N based 10T SRAM cell for wireless sensor network. (October 2019) - Sanvale, Prachi; Gupta, Neha; Neema, Vaibhav; Shah, Ambika Prasad; Vishvakarma, Santosh Kumar
Abstract: In this paper, a novel single ended PPN based 10T static random access memory (SRAM) with high read stability is presented. The proposed cell is energy efficient with double ended write, and single-ended read decoupled circuit for wireless sensor networks. The proposed 10T SRAM cell has a significant improvement in READ and WRITE stability with the least energy consumption. To evaluate the performance of the cells static noise margin, delay, power dissipation, leakage current, and area are calculated using the cadence environment at a standard CMOS 45 nm process technology. The simulation results show that it has enhancement of 83.4%, 50.14%, 43.3%, 50.14% and 3.09% on read SNM when compared with the conventional 6T, ST11T, ST1, ST2, and PPN 10T respectively at 1 V supply voltage. The proposed cell also achieves write SNM of 1.29×, 1.12×, and 1.18× higher compared to 6T, PPN10T, and ST11T, respectively. For a better perspective, we have proposed a figure of merit considering all the performance parameters, and it is observed that the proposed cell has better the FOM as compared to all other considered cells.